Implementasi PP No 24 Tahun 2018 Tentang Pelayanan Perizinan Berusaha Terintegrasi Secara Elektronik Atau Online Single Submission Dalam Meningkatkan Investasi Di Sumatera Barat - Upita Anggunsuri; shafira hijriya (Nagari Law Review, 2022)
Online Single Submission is a system developed by the government by reforming the administrative mechanism of business licensing services. The aim of this study is to find out the implementation of Government Regulation Number 24 Year 2018 concerning Electronic Business Licensing Services or Online Single Submission (OSS) fundamentally changing the permit issuance system from complicated to simple in West Sumatra. The method of research is empirical juridical. This research endeavours to answer the following questions : how to implement the Government Regulation Number 24 Year 2018 concerning Electronic Business Licensing Services to boost the investment in West Sumatra and what the obstacles faced in implementing Government Regulation Number 24 Year 2018 concerning Electronic Business Licensing Services to enhance the investment in West Sumatra and make the efforts to alleviate the issues. The result of this research shows that OSS has been implemented since 2018 in West Sumatra through the use of the OSS Version 1.0 application published by the Central Government. Furthermore, the implementation of OSS by the government of West Sumatra is also supported by the SIPSAKATO (SAKATO Licensing Information System) application related to addressing the essence of an integrated OSS system both at the Ministry level and the Regency or City levels. In practice, the implementation of OSS Version 1.0 had many weaknesses, thus the Government issued OSS version 1.1 to replace OSS Version 1.0. The use of the OSS Version 1.1 application is strengthened through the issuance of Government Regulation Number 5 Year 2021 concerning the Implementation of Risk-Based Business Licensing. The obstacles in the implementation of OSS in West Sumatra include the lack of understanding or education of the public regarding information on the licensing service process through OSS, as a result, it has logical consequences for the readiness of the government through related agencies on the importance of education and socialization to business actors due to the technical mechanism for digital licensing has an impact on the perception and readiness of business actors in implementing OSS. The availability of adequate human resources is expected to be able to provide the integrated education and socialization related to providing benefits, forming a positive perspective between agencies or institutions in communicating the role of OSS in economic growth. All stakeholders are expected to work together in supporting OSS system to improve the domestic and foreign investment in West Sumatera.